Repurchase Interest Using Shopeefood as an Impact of Online Customer Reviews and Promotions - Wati, Nur Sahara; Charisma, Dinna (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
Currently, online sales and purchases using electronic devices are very advanced and developing. The presence of Shopee, which is a buying and selling site, can make it easier for people to fulfill their needs and desires. This research aims to determine the condition of online customer reviews, promotions and repurchase interest on the Shopeefood application. This research uses a sample of 111 Instagram followers @nursaharaaa who use Shopeefood using descriptive and verification methods. The data collection technique used by researchers is by using primary and secondary data sources in the form of questionnaires. The analysis used is path analysis with the help of the SPSS program and hypothesis testing. The results of this research based on hypothesis testing show that Online Customer Reviews have a positive and significant effect on Repurchase Interest, Promotion has a positive and significant effect on Repurchase Interest, and Online Customer Reviews and Promotions simultaneously have a positive and significant effect on Repurchase Interest among Shopeefood application users.